'Meaningful participation': Exploring the value of limited participation for community radio listeners. (1st October 2019) - Backhaus, Bridget
Community radio represents an opportunity for audiences to play a lead role in the production, dissemination and ownership of media channels and content. The active participation of audiences is one of the primary differences between community radio stations and their commercial and state-run counterparts. The role of participation though is complicated in environments where community radio acts as an instrument for development, as is the case in India where community radio licenses are held by either educational establishments or non-governmental organizations (NGOs). Discussions around defining, encouraging and evaluating participation are extensive, yet little has been written about what defines meaningful participation from the perspective of community members. Drawing on ethnographic fieldwork in India, this article explores what makes participation meaningful and who is able to engage in this meaningful participation with community radio stations. Applying this perspective to community radio, encourages a more qualitative, holistic view of the benefits and outcomes of those who participate. Considering meaningful rather than maximalist or minimalist allows space to explore the impacts of participation in environments where it may be limited or restricted by structural factors. Engaged, invested audiences who regularly and meaningfully participate in their stations can help ensure that community radio remains a collaborative and powerful force within the global media landscape.